POLITICAL CULTURE STRATEGY IN CONFIGURATION OF ALTERNATIVE POLITICAL ELITES - Sahabuddin, Chuduriah; Amir, Arfenti; Tone, Kamaruddin; Yakin, Ahmad Al; Ishak, Suryadi (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to describe the political phenomenon clan-based politics with an imbalanced contestation process and the right strategy of political culture to issue alternative of political elites in Polewali Mandar which is not clan oriented. The research method used was qualitative phenomenology with epoche and eidetic. Epoche in phenomenology is a conceptualized assessment which must be postponed or given brackets until that phenomenon talks for itself while eidetic is the understanding of meaning always obtained and only through the understanding of expressions. The cultural strategy in the political arena of Polewali Mandar is a sequence of efforts done by politicians as alternatives for decreasing clan political power. Data in the field show there are two cultural strategies being able to reduce 3M Clan political power. Those two strategies are the reinforcement of medium intellectual group networks and strengthening the cohesiveness of alternative politicians. This research gives a contribution towards the implication of sociology theory with characteristics such as deterministic-dualism and the relation of this research finding towards bourdieau’s sociology theory, and the implication towards the development of sociology knowledge. This research gives a new perspective about the phenomenon of elite political configuration especially in the field of sociology and strategy of political culture.